TRADISI PERNIKAHAN PADA BULAN SYAWAL DI MADURA: KAJIAN LIVING HADITH - Mohammad Subhan Zamzami (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2018)
Abstract This article attempts to reveal the tradition of marriage in the month of Shawwal in Pamekasan Sub-district of Pamekasan Madura Regency from 2013 to 2017 in terms of the procedures. This article is the result of field research using phenomenology and living hadith approach. This research succeeded in revealing that the tradition of marriage in the month of Shawwal is one of Madurese wedding forms which has been going on downhill and deeply rooted in a society whose way of determining and the view of its existence varies so it is not realized as one of the socio-religious practices that is actually influenced by Islamic marriage tradition whose existence is derived from the hadith of the Prophet. Abstrak Artikel ini berusaha mengungkap tradisi pernikahan pada bulan Syawal di Kecamatan Pamekasan Kabupaten Pamekasan Madura sejak tahun 2013 hingga tahun 2017 dari segi tata caranya. Artikel ini merupakan hasil penelitian lapangan yang menggunakan pendekatan fenomenologi dan living hadith. Penelitian ini berhasil mengungkap tradisi pernikahan pada bulan Syawal termasuk salah satu bentuk tradisi pernikahan Madura yang sudah berlangsung secara turun-menurun dan mengakar kuat di tengah masyarakat yang cara penentuan dan pandangan tentang eksistensinya beragam, sehingga tidak disadari sebagai salah satu praktik sosial-keagamaan yang sebenarnya dipengaruhi oleh tradisi pernikahan Islam yang eksistensinya berasal dari hadis Nabi.